Dr Kazuo Inamori’s Management Praxis and Philosophy A Response to the Profit-Maximisation Paradigm - Kase, Kimio; Choi, Eugene; Nonaka, Ikujiro (The Nonaka Series on Knowledge and Innovation, 2022)
XXXI, 561 p. 32 illus., 12 illus. in color.